Role of Astrocytes in Central Respiratory Chemoreception - Eugenin-Leon, J; Beltran-Castillo, S; Olivares-Arce, M (Springer New York LLC, 2016)
Astrocytes perform various homeostatic functions in the nervous system beyond that of a supportive or metabolic role for neurons. A growing body of evidence indicates that astrocytes are crucial for central respiratory chemoreception. This review presents a classical overview of respiratory central chemoreception and the new evidence for astrocytes as brainstem sensors in the respiratory response to hypercapnia. We review properties of astrocytes for chemosensory function and for modulation of the respiratory network. We propose that astrocytes not only mediate between CO2/H+ levels and motor responses, but they also allow for two emergent functions: (1) Amplifying the responses of intrinsic chemosensitive neurons through feedforward signaling via gliotransmitters and; (2) Recruiting non-intrinsically chemosensitive cells thanks to volume spreading of signals (calcium waves and gliotransmitters) to regions distant from the CO2/H+ sensitive domains. Thus, astrocytes may both increase the intensity of the neuron responses at the chemosensitive sites and recruit of a greater number of respiratory neurons to participate in the response to hypercapnia. © Springer International Publishing Switzerland 2016.